Different Inflammatory Signatures in Alzheimer's Disease and Frontotemporal Dementia Cerebrospinal Fluid. - Boström, Gustaf; Freyhult, Eva; Virhammar, Johan; Alcolea, Daniel; Tumani, Hayrettin; Otto, Markus; Brundin, Rose-Marie; Kilander, Lena; Löwenmark, Malin; Giedraitis, Vilmantas; Lleo, Alberto; von Arnim, Christine A F; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Neuroinflammatory processes are common in neurodegenerative diseases such as Alzheimer's disease (AD) and frontotemporal dementia (FTD), but current knowledge is limited as to whether cerebrospinal fluid (CSF) levels of neuroinflammatory proteins are altered in these diseases. OBJECTIVE: To identify and characterize neuroinflammatory signatures in CSF from patients with AD, mild cognitive impairment (MCI), and FTD. METHODS: We used proximity extension assay and ANOVA to measure and compare levels of 92 inflammatory proteins in CSF from 42 patients with AD, 29 with MCI due to AD (MCI/AD), 22 with stable MCI, 42 with FTD, and 49 control subjects, correcting for age, gender, collection unit, and multiple testing. RESULTS: Levels of matrix metalloproteinase-10 (MMP-10) were increased in AD, MCI/AD, and FTD compared with controls (AD: fold change [FC] = 1.32, 95% confidence interval [CI] 1.14-1.53, q = 0.018; MCI/AD: FC = 1.53, 95% CI 1.20-1.94, q = 0.045; and FTD: FC = 1.42, 95% CI 1.10-1.83, q = 0.020). MMP-10 and eleven additional proteins were increased in MCI/AD, compared with MCI (q < 0.05). In FTD, 36 proteins were decreased, while none was decreased in AD or MCI/AD, compared with controls (q < 0.05). CONCLUSION: In this cross-sectional multi-center study, we found distinct patterns of CSF inflammatory marker levels in FTD and in both early and established AD, suggesting differing neuroinflammatory processes in the two disorders.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognitive Dysfunction; Cross-Sectional Studies; Female; Frontotemporal Dementia; Humans; Inflammation; Male; Middle Aged; Peptide Fragments; tau Proteins

Glial Fibrillary Acidic Protein in Serum is Increased in Alzheimer's Disease and Correlates with Cognitive Impairment. - Oeckl, Patrick; Halbgebauer, Steffen; Anderl-Straub, Sarah; Steinacker, Petra; Huss, André M; Neugebauer, Hermann; von Arnim, Christine A F; Diehl-Schmid, Janine; Grimmer, Timo; Kornhuber, Johannes; Lewczuk, Piotr; Danek, Adrian; et al. (J Alzheimers Dis, 2019)
Reliable blood biomarkers for Alzheimer's disease (AD) are missing. We measured astroglial GFAP in patients with AD (n = 28), frontotemporal dementia (bvFTD, n = 35), Parkinson's disease (n = 11), Lewy body dementias (n = 19), and controls (n = 34). Serum GFAP was increased in AD (p < 0.001) and DLB/PDD (p < 0.01), and cerebrospinal fluid GFAP was increased in all neurodegenerative diseases (p < 0.001). Serum GFAP correlated with the Mini-Mental State Examination score (r= -0.42, p < 0.001) and might be a follow-up marker in clinical trials. Sensitivity and specificity of serum GFAP for AD versus bvFTD was 89% and 79% and might be the first blood biomarker in the differential diagnosis of AD and bvFTD.

Novel Blood-Based Biomarkers of Cognition, Stress, and Physical or Cognitive Training in Older Adults at Risk of Dementia: Preliminary Evidence for a Role of BDNF, Irisin, and the Kynurenine Pathway. - Küster, Olivia C; Laptinskaya, Daria; Fissler, Patrick; Schnack, Cathrin; Zügel, Martina; Nold, Verena; Thurm, Franka; Pleiner, Sina; Karabatsiakis, Alexander; von Einem, Björn; Weydt, Patrick; Liesener, André; et al. (J Alzheimers Dis, 2017)
Psychosocial stress and physical, cognitive, and social activity predict the risk of cognitive decline and dementia. The aim of this study was to elucidate brain-derived neurotrophic factor (BDNF), irisin, and the kynurenine pathway (KP) as potential underlying biological correlates. We evaluated associations of irisin and the KP with BDNF in serum and with cognition, stress, and activities. Furthermore, changes in serum concentrations of BDNF, irisin, and KP metabolites were investigated after physical or cognitive training. Forty-seven older adults at risk of dementia were assigned to 10 weeks of physical training, cognitive training, or a wait-list control condition. Previous physical, cognitive, and social activities and stressful life events were recorded; global cognition, episodic memory, and executive functions were assessed. Serum levels of L-kynurenine, kynurenic acid, 3-hydroxykynurenine (3-HK), and quinolinic acid (QUIN) were determined by validated assays based on liquid chromatography coupled to tandem mass spectrometry. BDNF and irisin serum levels were determined with enzyme-linked immunosorbent assays. BDNF and irisin correlated positively with global cognition and episodic memory, while the neurotoxic metabolite QUIN correlated negatively with executive functions. Stressful life events were associated with reduced BDNF and increased 3-HK. 3-HK decreased after cognitive training, while BDNF tended to increase after physical training. This suggests that psychosocial stress as well as cognitive and physical training may impact BDNF serum levels and the KP. Irisin and QUIN may constitute novel serum biomarkers of cognitive impairment, in addition to BDNF. Larger scale trials are needed to replicate and extend these novel findings.

Cognitive Reserve in Alzheimer's Dementia: Diagnostic Accuracy of a Testing-the-Limits Paradigm. - Küster, Olivia C; Kösel, Jonas; Spohn, Stephanie; Schurig, Niklas; Tumani, Hayrettin; von Arnim, Christine A F; Uttner, Ingo (J Alzheimers Dis, 2016)
Individuals with higher cognitive reserve are more able to cope with pathological brain alterations, potentially due to the application of more efficient cognitive strategies. The extent to which an individual's cognitive performance can be increased by advantageous conditions differs substantially between patients with Alzheimer's dementia (AD) and healthy older adults and can be assessed with the Testing-the-Limits (TtL) approach. Thus, TtL has been proposed as a tool for the early diagnosis of AD. Here, we report the diagnostic accuracy of a memory TtL paradigm to discriminate between AD patients and controls. The TtL paradigm was administered to 57 patients with clinically diagnosed AD and 94 controls. It consisted of a pre-test condition, representing baseline cognitive performance, the presentation of an encoding strategy, and two subsequent post-test conditions, representing learning potential. Receiver operating characteristic (ROC) curves were analyzed for each condition in order to receive optimal cutoff points along with their sensitivity and specificity and to compare the diagnostic accuracy of the conditions. Differentiation between AD patients and controls, indicated by the area under the ROC curve, increased significantly for the TtL post-test and total error scores compared to the pre-test score. The combined error score in the two post-tests could differentiate between AD patients and controls with a sensitivity of 0.93 and a specificity of 0.80. The presented approach can be carried out in 25 minutes and thus constitutes a time- and cost-effective way to diagnose AD with high accuracy.